A study of role of technologies in the road freight transportation operations: from resources view to capabilities view - Callefi, Mario Henrique Bueno Moreira (Universidade Federal de São Carlos, 2023)
The road freight transportation activity is highly relevant nowadays, both financially and socially, since human survival depends on the resources transported by road freight transportation. However, cargo transport also has negative impacts, mainly due to the high emission of polluting gases, congestion and traffic accidents. Thus, it is essential to adopt technologies to make road freight transportation more efficient from an operational point of view and make it more sustainable. Knowing that technologies play an important role in road freight transportation, it was identified in the literature that technologies enable specific capabilities for road freight transportation. Thus, the main objective of this thesis is to study the role of capabilities enabled by technology in the road freight transportation system. To achieve these goals, three basic steps are taken. The first stage comprises a multimethod study to identify the capabilities enabled by technology in the road freight transportation system and verify the technological readiness level (TRL) of these capabilities based on secondary data. At this stage, 32 capabilities enabled by technology in the road freight transportation system were identified and organized into six categories (transport infrastructure; transport information; transport management; transport operation; transport monitoring; transport sustainability). In the second stage, the cause-and-effect associations between the resources enabled by the technologies for managing road freight transportation operations were analyzed. For the study of capabilities related to operations management, we used a mixed method approach based on three basic steps: identification and validation of technology-enabled data visibility capabilities; cause and effect association analysis; construction of technology-enabled capabilities framework for data visibility in road freight operations. As a result of the study, a framework was built with 11 technology-enabled capabilities for data visibility in road freight transportation operations. In the third stage of the study, the cause-and-effect associations between technology-enabled data visibility features in road freight transportation operations were analyzed. Basically, the same research method as in the second stage was used in this third stage of the study. The result of this step is a framework with 12 technology-enabled capabilities related to road freight transportation management, and a framework for classifying these capabilities was proposed. Finally, based on the analysis of the three stages of the study, a final conceptual model was proposed, systematizing the results obtained. This conceptual model presents three basic steps: (1) identification of capabilities related to the considered performance factor; (2) identification of which capabilities should be prioritized; (3) identification of which technologies should be prioritized.
Um estudo do papel das tecnologias nas operações do transporte rodoviário de carga: da visão de recursos para a visão de capabilities
Keywords: Road freight transportation; Information and communication technology; Capability; Transport technologies; Intelligent transportation systems; Smart technologies; Transporte Rodoviário de Cargas; Tecnologia da informação e Comunicação; Capabilidade; Tecnologias de transporte; Sistemas de transporte inteligentes; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO